A truncated AdeS kinase protein generated by ISAba1 insertion correlates with tigecycline resistance in Acinetobacter baumannii. - Jun-Ren Sun; Cherng-Lih Perng; Ming-Chin Chan; Yuji Morita; Jung-Chung Lin; Chih-Mao Su; Wei-Yao Wang; Tein-Yao Chang; Tzong-Shi Chiueh (PLoS ONE, 2012)
Over-expression of AdeABC efflux pump stimulated continuously by the mutated AdeRS two component system has been found to result in antimicrobial resistance, even tigecycline (TGC) resistance, in multidrug-resistant Acinetobacter baumannii (MRAB). Although the insertion sequence, ISAba1, contributes to one of the AdeRS mutations, the detail mechanism remains unclear. In the present study we collected 130 TGC-resistant isolates from 317 carbapenem resistant MRAB (MRAB-C) isolates, and 38 of them were characterized with ISAba1 insertion in the adeS gene. The relationship between the expression of AdeABC efflux pump and TGC resistant was verified indirectly by successfully reducing TGC resistance with NMP, an efflux pump inhibitor. Further analysis showed that the remaining gene following the ISAba1 insertion was still transcribed to generate a truncated AdeS protein by the Pout promoter on ISAba1 instead of frame shift or pre-termination. Through introducing a series of recombinant adeRS constructs into a adeRS knockout strain, we demonstrated the truncated AdeS protein was constitutively produced and stimulating the expression of AdeABC efflux pump via interaction with AdeR. Our findings suggest a mechanism of antimicrobial resistance induced by an aberrant cytoplasmic sensor derived from an insertion element.